EFEKTIVITAS PPKM DARURAT DAN PPKM LEVEL 2, 3 dan 4 DALAM MENURUNKAN PASIEN AKTIF COVID-19 DI INDONESIA: Measuring The Effectiveness of PPKM In Reduce Active Covid-19 Patients In Indonesia - nurul istiqomah (BPS Kalimantan Timur, 2022)
The Covid-19 pandemic not only has an impact on the Indonesian economy, but also has a social impact on people's lives. To suppress active cases of Covid-19, the government has issued several regulations, such as vaccination and implementation of PPKM. After the emergency PPKM, the government again implemented the PPKM level 2,3, and 4 policies which were implemented in stages through the Instruction of the Minister of Home Affairs. The determination of this level is based on tightening or easing public health efforts and social restrictions based on WHO standards. This study aims to see the effectiveness of the policy in reducing active cases of Covid-19 using a paired sample test. Testing is carried out on the number of active Covid-19 cases before and after the enactment of policies or regulations. Based on the paired sample test, several conclusions were obtained, including the emergency PPKM ineffective in reducing active cases of Covid-19 in the Java and Bali regions. In contrast to the previous policy, PPKM levels 2,3, and 4 are effective in reducing active cases of Covid-19, although slowly. For the Java and Bali regions, this policy was effective at the end of stage 4. While in areas outside Java-Bali, PPKM levels 2,3, and 4 significantly reduced active cases of Covid-19 at stage 5. The success of the Indonesian government has been appreciated by John Hopkins University CSSE Covid-19 as one of the best in the world, a country that has succeeded in suppressing the transmission of Covid-19.